Does Land Fragmentation Increase the Cost of Cultivation? : Evidence from India - Deininger, Klaus; Monchuk, Daniel; Nagarajan, Hari K.; Singh, Sudhir K. (Taylor and Francis, 2016)
To appreciate overall impacts of fragmentation, underlying channels, and potential heterogeneity by holding size, we distinguish average fragment size and mean inter-fragment distance as two aspects of this phenomenon. Estimating a cost function with associated input demand equations on a large nationally representative Indian survey, robust to endogeneity, suggests that fragmentation’s main impact is to reduce mean plot size below the threshold for mechanization. Higher inter-fragment distances increase costs for larger holdings, but by a much smaller magnitude. Implications as to when programs to consolidate holdings may make sense and ways to ensure their sustainability are discussed.